Only fear the fatal foe: predation risk assessment by eastern newts (Notophthalmus viridescens) in response to common snapping turtles and other potential predators. Issue 3 (4th May 2017) - Chapman, Trevor L.; Spivey, Kari L.; Lundergan, Jennifer M.; Schmitz, Alexandra L.; Bast, Derek L.; Sehr, Evie K.; Gall, Brian G.
Abstract : Many organisms utilize toxic or noxious compounds as a means of deterring predation. Eastern newts ( Notopthalmus viridescens ), along with other species in the family Salamandridae, possess a potent neurotoxin called tetrodotoxin (TTX). Although TTX can serve as an effective antipredator mechanism in species of newts with high concentrations (e.g., Taricha ), eastern newts have relatively low levels of toxicity in comparison to those species, and it may not serve as an effective antipredator mechanism against all threats. In this case, they may benefit rather by utilizing behavioral changes to avoid initial contact with predators. We tested for predator-avoidance behavior in newts by exposing individuals to kairomones from various predators. We recorded activity patterns of newts when they were exposed to cues from potential predators including bullfrogs ( Lithobates catesbeiana ), water snakes ( Nerodia sipedon ) and snapping turtles ( Chelydra serpentina ), as well as a non-predator (bullfrog tadpoles), and a control (deionized water). Newts reduced activity when exposed to snapping turtle stimuli, but did not change activity when exposed to any other chemical cues. We verified that newts interact with this predator by trapping snapping turtles found in ponds from which newts were collected. Finally, we used turtles caught during this sampling to test whether they are an actual predator of newts and whether newts shift microhabitat use when exposed to this predator. In each replicate, turtles consumed newts, and newts spatially avoided the snapping turtle, relative to a control. The results of these experiments indicate newts rely on predator-avoidance behavior to reduce the probability of being consumed by snapping turtles, but do not reduce activity in response to other potential predators that may only consume them rarely.